Influence of Pulsed Electromagnetic Field on Plant Growth, Nutrient Absorption and Yield of Durum Wheat - Nikolaos KATSENIOS; Victor KAVVADIAS; Sideris THEOCHAROPOULOS; Dimitrios BILALIS; Zaharias IOANNOU; Antonios PAPADOPOULOS; Nektaria LIAKOPOULOU (Notulae Scientia Biologicae, 2015)
Researchers have adopted the use of magnetic field as a new pre-sowing, environmental friendly technique. Enhancements on plant characteristics with economic impact on producer’s income could be the future of a modern, organic and sustainable agriculture. A field experiment was established at Soil Science Institute of Athens, Lycovrissi, Greece, in the winter of 2014. Two durum wheat cultivars were used. It was a pot experiment with 6 treatments (2 cultivars with 3 magnetic field time exposure). The seeds were treated using a PAPIMI electromagnetic field generator for 0, 30 and 45 minutes one day before planting. The experiment followed a completely randomized design with six treatments and 30 replications. The aim of this study was to evaluate the positive effect of magnetic field pre-sowing treatment in a wide range of plant measurements, including yield. The influence of pulsed electromagnetic field on two varieties of durum wheat seeds showed some statistically significant differences at the 0.05 level in growth measurements, physiological measurements and root growth measurements. Plant tissue analysis showed that magnetic field treatments had higher values than control in total nitrogen, phosphorus, potassium, magnesium, copper (only MF-45), zinc (only MF-30) and boron content, although values showed statistically significant differences only in total nitrogen. The results indicate that this innovative technique can increase the yield of durum wheat, through enhanced absorption of nutrients. Pre-sowing treatment of the seeds leads to vigorous plant growth that are more productive.